Neutral Functional Partial Differential Equations Driven by Fractional Brownian Motion with Non-Lipschitz Coefficients (Journal of Partial Differential Equations, 2014)
" Under a non-Lipschitz condition being considered as a generalized case of Lipschitz condition, the existence and uniqueness of mild solutions to neutral stochastic functional differential equations driven by fractional Brownian motion with Hurst parameter 1\/2 \u2039 H \u2039 1 are investigated. Some known results are generalized and improved."
Keywords: Neutral functional partial differential equation; mild solution; Wiener integral; fractional Brownian motion